2020
DOI: 10.3389/fpls.2020.00780
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Summer Dormancy of Pinellia ternata by Introducing a Heat Tolerance Receptor-Like Kinase ERECTA Gene

Abstract: Breaking Summer Dormancy of P. ternata 5, 9-trimethyl-12-(1-methylethyl). Our findings show that the summer dormancy of P. ternata which is a naturally evolved trait, can be removed by a single heat responsive gene. The study contributes to generating heat tolerant new Pinellia varieties with enhanced commercially valuable chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The growth in tuber biomass of P. ternata in soil (regardless of biochar application rate) is more than the growth of the same species in a chemical growth media (Kim et al, 2020). Only in case of biochar application in CDG, the tuber growth was more or comparable to genetically modified P. ternata reported by Juneidi et al (2020). The tuber biomass was relatively lower for laterite as compared to CDG at the same biochar application rate.…”
Section: Effects Of Biochar On Root Tuber Biomass Root Length and Tub...mentioning
confidence: 75%
See 1 more Smart Citation
“…The growth in tuber biomass of P. ternata in soil (regardless of biochar application rate) is more than the growth of the same species in a chemical growth media (Kim et al, 2020). Only in case of biochar application in CDG, the tuber growth was more or comparable to genetically modified P. ternata reported by Juneidi et al (2020). The tuber biomass was relatively lower for laterite as compared to CDG at the same biochar application rate.…”
Section: Effects Of Biochar On Root Tuber Biomass Root Length and Tub...mentioning
confidence: 75%
“…Moreover, incessant cultivation of this medicinal plant from its natural wild resources further leads to a loss of genetic diversity and habitat destruction of other native plants (Canter et al, 2005). It has also been recently reported that P. ternata showed a decrease in yield or even die during summer seasons in agricultural fields due to climate change (Juneidi et al, 2020). The plants are shade tolerant up to 50% to 100% (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The commercial clinically hypolipidemic drugs Simvastatin often cause undesirable adverse effects such as rhabdomyolysis [ 23 ]. Therefore, many Chinese herbal medicines have antihyperlipidemic effects [ 24 , 25 ], and the possible effective components might be polysaccharides. In our research, the antihyperlipidemic activities of Radix trichosanthis polysaccharides were explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the importance of multi-functional ER genes in plant development and in response to environmental changes [325]. To break summer dormancy and to provide heat tolerance, Juneidi et al [287] introduced a heat responsive ER gene into the Chinese medicinal plant, Pinellia ternata. The transgenic lines were better adapted to heat stress.…”
Section: Temperature Stressmentioning
confidence: 99%